Effects of parsley (Petroselinum crispum) extract versus glibornuride on the liver of streptozotocin-induced diabetic rats - YARAT, AYŞEN; AKBAY, TUĞBA (ELSEVIER IRELAND LTD, 2006)
Parsley (Petroselinum crispum) is one of the medicinal herbs used by diabetics in Turkey. The aim of this study is to investigate the effects of parsley (2 g/kg) and glibornuride (5 mg/kg) on the liver tissue of streptozotocin-induced diabetic rats. Swiss albino rats were divided into six groups: control; Control + parsley; control + glibornuride; diabetic; diabetic + parsley; diabetic + glibornuride. Diabetes was induced by intraperitoneal injection of 65 mg/kg streptozotocin (STZ). Parsley extract and glibornuride were given daily to both diabetic and control rats separately, until the end of the experiment, at day 42. The drugs were administered to one diabetic and one control group from days 14 to 42. On day 42, liver tissues were taken from each rat. In STZ-diabetic group, blood glucose levels, serum alkaline phosphatase activity, uric acid, sialic acid, sodium and potassium levels, liver lipid peroxidation (LPO), and non-enzymatic glycosylation (NEG) levels increased, while liver glutathione (GSH) levels and body weight decreased. In the diabetic group given parsley, blood glucose, serum alkaline phosphatase activity, sialic acid, uric acid, potassium and sodium levels, and liver LPO and NEG levels decreased, but GSH levels increased. The diabetic group, given glibornuride, blood glucose, serum alkaline phosphatase activity, serum sialic acid, uric acid, potassium, and liver NEG levels decreased, but liver LPO, GSH, serum sodium levels, and body weight increased. It was concluded that probably, due to its antioxidant property, parsley extract has a protective effect comparable to glibornuride against hepatotoxicity caused by diabetes. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: parsley; glibornuride; streptozotocin; liver; serum; BLOOD-GLUCOSE; SIALIC-ACID; SERUM; PLANTS; LEAVES; LIPIDS